COMPONENTS OF SUSTAINABLE DEVELOPMENT IN THE CONTEXT OF MODERN CHALLENGES - Мандич, Олександра; Бабко, Наталя; Накісько, Олександр; Бірченко, Наталія; Гіржева, Ольга (SWorldJournal, 2023)
Problems of sustainable development are always in the center of attention of science and business. However, the very essence, factors and main characteristics of these phenomena are not always obvious and require further research. The COVID-19 pandemic a